Photo-Assisted Flexible Energy Storage Devices: Progress, Challenges, and Future Prospects - Jiang, Xupu; Ding, Ting; Wang, Rui; Ma, Wujun; Jiang, Xupu; Lan, Chuntao; Li, Min; Zhu, Meifang (Nano-Micro Letters, 2026)
Photo-assisted flexible energy storage devices, combining photoelectric conversion and electrochemical energy storage, emerge as an innovative solution for sustainable energy systems. This review comprehensively summarizes recent advances in photo-assisted flexible energy storage technology, covering material design, working mechanisms, and practical applications. We systematically examine diverse electrode materials, such as metal oxides, metal sulfides, organic photosensitive materials, and composites, emphasizing their roles in boosting device performance. Special focus is placed on emerging technologies—including heterostructure engineering, surface modification, and intelligent control systems—that have notably enhanced energy conversion efficiency and storage capacity. The review also discusses current challenges, such as material stability, conversion efficiency, and standardization, and proposes strategic directions for future development. Recent breakthroughs in photo-assisted supercapacitors, lithium-based batteries, zinc-based batteries, and other innovative storage systems are critically assessed, offering key insights into their practical application potential in wearable electronics, self-powered sensors, and beyond. This comprehensive analysis establishes a framework for understanding the current status of photo-assisted flexible energy storage technology and guides future research toward high-performance, sustainable energy storage solutions. Highlights: 1 This review provides a comprehensive integration of photoconversion and electrochemical storage mechanisms for flexible wearable applications. 2 It systematically classifies and compares various flexible light-assisted energy storage systems—from supercapacitors to diverse metal batteries—within a unified framework. 3 The review highlights advanced material design strategies and performance enhancement techniques specifically tailored for light-responsive energy storage, including heterojunctions, doping, and nanostructures.